ABOUT TEACHING METHODS FOR SOLVING TEXT TASKS IN THE COURSE OF ALGEBRA - Nurbayeva Д.М.; Nurmukhamedova Ж.М.; Yerzhenbek Б.; Nassirova Д.М. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2021)
The article is devoted to the solution of text tasks in the course of algebra. Recently, it has been observed that the solution of text tasks causes difficulties not only for schoolchildren, but also there are cases when the solution of such problems causes problems for practicing mathematics teachers. Therefore, in the article, we have considered several types of tasks for which solutions have been proposed, which we consider useful material for preparing existing teachers for algebra lessons, when studying the topics of solving text tasks using equations and their systems. Also, reading this article is recommended for students-future teachers of mathematics before or during their teaching practice. The article does not contain solutions to equations and their systems, since the purpose of this article is to teach how to make equations and systems of equations for solving text tasks, and not to solve them. For the design of the task conditions, both drawings, tables, and just writing short conditions are used.